2020
DOI: 10.1097/scs.0000000000006343
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Mandibular Distraction Osteogenesis in Infants With Pierre Robin Sequence

Abstract: Pierre Robin sequence is the constellation of micrognathia, glossoptosis, and tongue-based airway obstruction. When airway obstruction is severe, feeding, growth, and respiratory demise are at risk. Neonatal mandibular distraction osteogenesis is a technique which improves tongue-based airway obstruction and avoids tracheostomy in patients with severe expressions of Pierre Robin sequence. Its efficacy in relieving airway obstruction is well documented, and it has become the surgical intervention of choice at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…While several other studies have reported the use of PSG pre- and post-operatively in their management of patients undergoing MDO, few have identified using the study results to affect decisions regarding distraction phase. 13,14,25 Repeat distraction rates have been reported in 6% of cases, while relapse rates are cited as high as 64%. 7,26-28 However, some argue that relapse is an inevitable consequence of operating on the skeletally immature patient who may continue to have asynchronous growth of the mandible and maxilla even after distraction.…”
Section: Discussionmentioning
confidence: 99%
“…While several other studies have reported the use of PSG pre- and post-operatively in their management of patients undergoing MDO, few have identified using the study results to affect decisions regarding distraction phase. 13,14,25 Repeat distraction rates have been reported in 6% of cases, while relapse rates are cited as high as 64%. 7,26-28 However, some argue that relapse is an inevitable consequence of operating on the skeletally immature patient who may continue to have asynchronous growth of the mandible and maxilla even after distraction.…”
Section: Discussionmentioning
confidence: 99%
“…Though distractors are not typically used for this type of defect rather for congenital conditions such as Pierre-Robin Sequence or hemifacial microsomia, we adapted these techniques to this patient’s condition. 23,25-27 For direct visualization and to maintain intra-oral mucosal integrity we used an extra-oral approach and we applied a linear distraction movement rather than a curve. Once placed, there was a latency period of 5 days and then 0.5 mm of distraction twice daily until approximately 40 mm was reached.…”
Section: Case Reportmentioning
confidence: 99%
“…For JHH and JH-ACH patients not requiring intubation or tracheostomy prior to surgery, polysomnography was obtained to evaluate the severity of obstructive sleep apnea (OSA; typically obstructive apnea-hypopnea index [AHI] ! 20 for patients proceeding to MDO) and rule out a significant central component (Diep et al, 2020). Bedside flexible laryngoscopy was generally performed prior to surgery.…”
Section: Mandibular Distraction Osteogenesis Protocolmentioning
confidence: 99%
“…The small, posteriorly positioned mandible is inadequate in supporting the soft tissues of the oropharynx and tongue, causing the tongue to fall back into the pharynx and occlude the upper airway (Evans et al, 2011). Mandibular distraction osteogenesis (MDO) has now been adopted as the first-line surgical therapy at many centers and aims to reposition the tongue anteriorly through its attachments to the mandible, effectively increasing the anteroposterior diameter of the infant's airway (Bangiyev et al, 2016;Khansa et al, 2017;Susarla et al, 2018;Bekisz et al, 2020;Diep et al, 2020).…”
Section: Introductionmentioning
confidence: 99%